Observation and manipulation of glial cell function by virtue of sufficient probe expression - Natsubori, Akiyo; Takata, Norio; Tanaka, Kenji F. (Frontiers in Cellular Neuroscience, 2015)
The development of gene-encoded indicators and actuators to observe and manipulate cellular functions is being advanced and investigated. Expressing these probe molecules in glial cells is expected to enable observation and manipulation of glial cell activity, leading to elucidate the behaviors and causal roles of glial cells. The first step toward understanding glial cell functions is to express the probes in sufficient amounts, and the Knockin-mediated ENhanced Gene Expression (KENGE)-tet system provides a strategy for achieving this. In the present article, three examples of KENGE-tet system application are reviewed: depolarization of oligodendrocytes, intracellular acidification of astrocytes, and observation of intracellular calcium levels in the fine processes of astrocytes.